ORGANISATIONAL LEGITIMACY STRATEGIES IN A CONTEMPORARY WORLD: AN INVESTIGATION OF ENTREPRENEURS’ USE OF SOCIAL MEDIA TO GAIN AND MAINTAIN LEGITIMACY. - Gumbo, Ruvimbo (2012)
The advent of Internet has had a tremendous impact on the world as we once new it thirty years ago. Internet has become an essential part of the modern individual’s life changing the way they bank, shop and even date thus enabling numerous new opportunities. The internet has also changed the way businesses’ attract and communicate with their customers, thus even the smallest to largest organisation have felt the indelible impact of this new communication platform. What enables the Internet to have such far-reaching effects is its ability to unite millions of individuals across the globe at a little or no cost through various social media. Social media is basically a broad range of online applications that facilitate the sharing of text, photos and information with ease. Due to these mediums, most consumers are fully informed and customers have become extremely powerful because they have a platform to share the information they have with the entire world in a matter of seconds.